Performing from Heidegger's Turning. (1st July 2015) - Grant, Stuart
This article aims to do two things. (1) Describe aspects of the performance methodology and philosophy of the site-specific ecological performance group, the Environmental Performance Authority (EPA), in a series of performances entitled Coastal Scales, developed in conjunction with the Hobsons Bay Council in Melbourne, Australia. (2) Make an argument for the efficacy of the EPA's work, through concepts from Heidegger's later writings, with particular reference to the 'turning', and the occurrence of truth as the strife between earth and world, as developed in Contributions to Philosophy (1999, 2012) and 'The origin of the work of art' (1977a).